The Internationalization of Sharia-Based MSMEs in Indonesia: An Overview and Research Agenda - M. Elfan Kaukab (Faculty of Economics and Business Universitas Jenderal Soedirman, 2022)
Study on MSMEs internationalization is a research theme gaining more and more attention nowadays. This research aims to explore the state of the art of sharia MSMEs internationalization in Indonesia from both the government and scientific studies sides. The method applied is a literary review using grey literature of printed media and government’s official publication, and also scientific literature from the Google Scholar search engine. The result shows only three studies discuss very limited sharia MSMEs internationalization in Indonesia. From the grey literature, this research reveals that various government elements positively support the development of sharia MSMEs. This especially is shown from Indonesian Sharia Economy Masterplan 2019-2024 along with its heterogeneous implementation, including the plan to build a sharia business database in Indonesia. Furthermore, private parties also participate in boosting MSMEs internationalization. On the other hand, the development of sharia MSMEs internationalization studies is only at the early stage, similar to the government attention towards this business segment. Among the academics, this is due to the absence of theoretical frameworks that cover sharia MSMEs internationalization, whether in specific or general in sharia economics scope. It is also caused by the lack of well-structured MSMEs business performance database and the unobvious concepts of sharia MSMEs elements. Therefore, it is recommended that theoretical studies filling the gap, especially in economic aspects, such as financial resources flow as well as empirical studies such as survey, financing, innovation, and consumer’s determinant, are conducted.